Molecular dynamics simulations of DARPins as potential inhibitors against cancer associated protein kinases / Vertika Gautam - Vertika , Gautam (2021)
Out of all post-translational modifications, Protein phosphorylation is the most common in signal transduction, that occurs through protein kinases. Extracellular Regulated Kinase 2 (ERK2) is a type of protein kinase that undergoes phosphorylation to control various pathological and physiological phenomena. The deregulation of ERK2 often implicated in several types of cancers, for example, pancreatic, lung and breast. The current therapeutic treatment for this type of cancers involves blocking cellular proliferation signals by targeting kinases. However, the drugs developed resistance after prolonged use. Thus, the discovery of alternative ERK2 inhibitors is in need. In the present work, the potential of a class of repeat proteins - Designed Ankyrin Repeat Proteins (DARPins) is studied as ERK2 inhibitors, using computational chemistry approaches. The structural basis of ERK2-DARPin interactions based on molecular dynamic (MD) simulations and role of water molecules in the binding region of the protein-protein complexes was characterized using 3D Reference Interaction Site Model (3D-RISM). The information was then used in designing more DARPin mutants using single point mutations which were subsequently subjected to MD simulations and binding free energy calculations. Two mutants; A443D and S380L, were predicted to perform better than the original sequence (wild-type DARPin) based on the associated energy, the dynamics of global motions, and key residues involved in protein-protein interaction. This study showcases the use of computational chemistry tools in understanding proteinprotein interactions and designing specific inhibitors against cancer-associated protein kinases.